Інституційні механізми забезпечення кібербезпеки в Європейському Союзі - Кардаш, Оксана; Гладун, Любомир (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Проведено дослідження інституційних та організаційно-правових механізмів забезпечення кібербезпеки в Європейському Союзі. Здійснено аналіз співпраці Європейського Союзі з Україною і сфері кібербезпеки. Виокремлено основні загрози кіберпростору ЄС та механізми їх подолання. A study of institutional and organizational and legal mechanisms for ensuring cyber security in the European Union was conducted. An analysis of the European Union's cooperation with Ukraine and the field of cyber security was carried out. The main threats to the EU cyberspace and the mechanisms for overcoming them are highlighted.